Modelling Economic Growth Based on Factors of Innovation Production Potential Development - Derunova, Elena; Andryushchenko, Sergey; Derunov, Vladimir (International Journal of Engineering and Technology, 2018)
The Russian economic growth is associated with the increase in the competitive advantages of the domestic industry and the material sector of economy, including agriculture. The article studies the factors that have positive impact on the economic development and growth, as well as those that restrain these processes. The problem of assessing the need in innovative activity of economic sectors is actualized taking into account the differences of Russian regions in terms of agricultural productivity. The use of the imitations and innovationsâ€™ theory and methodological instruments of production functionsâ€™ models is substantiated. Thus, the Solow model is studied, and the improvement of the model, including the fundsâ€™ introduction delay when the optimal accumulation rates are equal to the elasticity coefficients by funds, is shown. The factors that include various economic growth models: volumes of capital, physical and intellectual labor, labor productivity, the production returns rate, the scientific and technological progress rate, the population growth rate, the consumer demand, production structure, institutional factors, and saving rates, are studied. It is proved that the study of neoclassical models of the economic growth shows their incomplete adequacy taking into account all differentiating factors, competitive processes and differentiating branch structures of economy. In the work, the hypothesis of the interrelationship of the saving rate, labor productivity and the volume of investments in Russia is mathematically proven taking into account the differentiation of Russian regions and peculiarities of statistical accounting.Â Â